A qualitative review and thematic synthesis of resident experiences in prison-based democratic therapeutic communities - Fernandes, Candida (The journal of forensic psychiatry & psychology, 2025)
A qualitative systematic review and thematic synthesis was conducted to explore residents’ perspectives of prison-based democratic therapeutic communities (DTCs). This is important to inform effective treatment for residents of these communities. Five databases were searched for studies published between January 1962 and November 2023. Following screening, eleven qualitative studies were included in the review. Collectively, the review sample were 153 male residents of prison-based DTCs. Three themes were generated by thematic synthesis: (1) The Importance of Safety in the Therapeutic Environment, (2) Opening Up to Vulnerability and (3) Life Within and Beyond the DTC. Experiences were highlighted within the papers reviewed where progress in each of these areas was comprised for some residents, due to inequalities, stigma, and disconnection. Further training and awareness to support residents who experience such difficulties is needed. Interventions within prison-based DTCs to help reduce toxic masculinity and promote emotional vulnerability are also recommended. In addition, there is a need for culturally informed and adapted practices to help those from minoritized background integrate into prison-based DTC communities. Further qualitative research across UK prison-based DTC settings incorporating the voices of those participating in therapeutic communities would be beneficial to expand the generalisability and diversity of findings.